Prevalence of anaemia and visual impairment among primary school children of Ahmedabad City, Gujarat: a cross sectional study - Gunjana, Geet; Upadhyay, Nisha; Dixit, Grishma; Thakor, Nilesh (International Journal of Contemporary Pediatrics, 2017)
Background: Nutritional anemia and visual impairment among school age children are recognized as public health problem worldwide. The objective of the study was to prevalence of anemia and visual impairment among school going adolescents of Ahmedabad city, Gujarat. Methods: This cross-sectional study was carried during period from January 2012 to March 2012. 4 schools were selected by purposive sampling. After taking the permission from principals of schools and informed written consent of the parents of the children, 421 children from these schools of Ahmedabad city were examined for anemia and visual impairment. The data was collected by predesigned, pretested performa and analyzed using Epi Info. Results: Out of total 421 children 205 (48.7%) were female. Mean age of the study children was 7.9 ± 1.06 years. The prevalence of anemia in children in present study was 61.9 % (261 children). The prevalence of anemia in female (134, 62.9%) was higher than males (130, 60.1%). Moderate to severe visual impairment and blindness was 7.2% in girls and 10.5% in boys respectively and the gender difference was not statistically significant. Though 38 (8.9%) children had moderate to severe visual impairment to blindness only 10 (2.3%) children were wearing spectacles. Conclusions: High prevalence of anemia and visual impairment among these children needs great attention and health education.